Acute Management of Massive Epistaxis After Nasotracheal Extubation - Kido, Kanta (Anesth Prog, 2019)
Epistaxis is one of the most common complications of nasotracheal intubation and can be life-threatening. However, there is little discussion in the current literature on the acute management of massive epistaxis after nasotracheal extubation. This is a report of 2 patients who experienced severe unanticipated nasal bleeding immediately after extubation, 1 after a surgical procedure for oral cancer and another after restorative dental treatment. In both cases the significant epistaxis was managed successfully with a Foley balloon catheter used to pack the posterior nasal cavity. The Foley catheter technique may be useful for managing and arresting sudden postextubation epistaxis.